Correlation of cost, time, need, access, and competence with the public interest in installing dentures at non-professional dentist - Yayah Sopianah; Muhammad Fiqih Sabilillah; Ayyu Fadilah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Tooth loss can be caused by trauma, caries, and periodontal disease. It then can trigger an emotional impact on each individual, such as having a lack of confidence, feeling ashamed of the appearance, and trying to hide the missing teeth. As a result, people experiencing tooth loss want to put or replace their missing teeth with artificial ones. Unfortunately, many of them prefer to visit non-professional dentists rather than professional ones providing the same services because of both internal and external factors. Purpose: This research aimed to analyze factors affecting the public interest in Losari District of Brebes Regency in 2016 to install dentures in non-professional dentists. Method: This research focused on a correlation of cost, time, need, access, and competence with denture-making care interest using survey method. Sampling was conducted with purposive sampling technique. The number of samples was thirty-six people. Result: There was a significant correlation between public interest in installing dentures at non-professional dentists and cost factor (a p value of 0.010, <a 0.05). Similarly, there was a significant correlation between public interest in installing dentures at non-professional dentists and time factor (a p value of 0.000, <a 0.05). There were significant correlations between the public interest in installing dentures at non-professional dentists and need (a p value of 0.004, <a 0.05), as well as between public interest in installing dentures at non-professional dentists and access factor (a p value of 0.000 <a 0.05). Nevertheless, there was no correlation between public interest in installing dentures at non-professional dentists and competence factor (a p value of 0.482> a 0.05). Conclusion: It can be concluded that there is a correlation between cost, time, need, and access with the public interest in installing dentures at non-professional dentists. Community competence has no correlation with public interest in installing dentures at non-professional dentists.